Medallion „Librarians in time and space”. Elena Farago (Confluenţe Bibliologice, 2025)
The article is a tribute to the poet Elena Farago, a prominent figure in Romanian literature. The author highlights not only Elena Farago's poetic talent, but also her involvement in the cultural life of Craiova, especially as director of the "Alexandru and Aristia Aman" Foundation. Through her work for over three decades within the library, Farago significantly contributed to its development, attracting valuable donations and organizing cultural activities.
Keywords: Farago Elena (1878 – 1954); Romanian literature